The Implementation of Electronic Certificates in Public Administration: Towards a Legal Framework that Supports Digital Inclusivity (Open Society Conference, 2025)
The digital transformation of state administration requires a robust and inclusive legal infrastructure, including the use of electronic certificates as a legal instrument in the digitization of public services. This study aims to analyze how Indonesia^s legal framework regulates and supports the use of electronic certificates in state administration and to what extent these regulations promote digital inclusivity across all segments of society. A normative juridical approach is employed, focusing on the analysis of relevant legislation such as the Electronic Information and Transactions Law (ITE Law), Government Regulation No. 71 of 2019, and related derivative regulations concerning digital signatures and electronic certificates. This research also examines implementation challenges, including digital access disparities, technological literacy, and infrastructure readiness. The findings indicate that while Indonesia has a sufficient normative legal foundation for the use of electronic certificates, technical, social, and geographic barriers remain that hinder inclusive implementation. Therefore, affirmative policy reinforcement and regulatory updates responsive to technological changes and societal needs are essential to ensure that digital transformation in public administration is truly inclusive and does not marginalize vulnerable groups.